Assessing Oral Mucosal Health: Secondary Bacterial Infections in Pediatric Patients with Type 1 Diabetes - Mohanty, Susant; Patra, Subhajit; Rath, Shakti; Das, Rupsa; Palai, Sourav; Singhsamanta, Debidatta (Bangladesh Journal of Infectious Diseases, 2025)
Background: Juvenile diabetes or Type 1 Diabetes (T1D) mellitus is an autoimmune-mediated disease resulting in insulin deficiency, and it is the second most frequent disease in children. T1D also affects the oral health of a child. Objectives: This current work was undertaken to characterise and compare the salivary microbiome of children with Type 1 Diabetes (T1D) and healthy controls while evaluating the influence of oral environmental factors such as DMFT index, salivary flow rate, and buffering capacity. Methodology: The study was a comparative cross-sectional study conducted at the Department of Pediatric and Preventive Dentistry and Central Research Laboratory, Institute of Dental Sciences, Siksha ‘O’ Anusandhan (Deemed to be University), Bhubaneswar, Odisha, during the period from October 2023 to March 2024. A total of 20 children (10 healthy individuals, 10 with TID) were selected. Detailed case history and DMFT/DMFS index were recorded. The saliva sample was collected from all patients and was analysed for pH and flow rate. The samples were processed for microbiological evaluation using routine microbiological procedures, and the isolated bacteria were subjected to antibiotic sensitivity tests. Results: Among 20 children, 10 (50%) had Type 1 Diabetes and 10 (50.0%) were healthy controls. The mean DMFT score was higher in the diabetic group (3.8 ± 1.03) compared to controls (2.8 ± 1.03), with a significant difference (p <0.05). Salivary flow rate, pH, and buffering capacity were lower in diabetic children (p < 0.01). The mean CFU count was higher in the diabetic group (20 ± 3.13) than in controls (11.4±2.46), showing significant variation (p < 0.05). Conclusion: Children with Type 1 Diabetes showed altered salivary microbiota, reduced salivary flow rate, buffering capacity, and lower pH, resulting in higher DMFT scores and bacterial counts compared to healthy children. Bangladesh Journal of Infectious Diseases, June 2025;12(1):141-150